Cross Cultural Communication: How Traveling Influences People’s Perspective in Seeing the World - Iin Rachmawati (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2018)
Nowadays, traveling has been transformed drastically into a-must-do activity to ensure that they can keep update on what’s trending now. Today there are a whole bunch of advertisements which attract people to go traveling the world. And this phenomenon is strengthen with the abundance amount of online traveling applications like Traveloka, PegiPegi, Tiket.com, Agoda, Airy, AirBnb, and many more lists which make traveling become much more practice and pretty easier. Based on those facts, this research aims to explore more about how big the influence of the advertisements and online traveling applications will affect people to go traveling as well as to examine about about the ways traveling influences people’s perspective in seeing the world. This research used ethnomethodology as the research design since it discusses much about the traveling phenomenon in relation with people’s perspective and response in seeing the world outside. The data were gathered through online questionnaire in the Facebook group of ‘Backpacker Dunia’ which consist of twenty submitted questionnaires. Personal data analysis (through questionnaire and interviews) was performed to test whether the influence of advertisements and online traveling applications will affect people to go traveling and whether traveling influences people’s perspective in seeing the world or not. The data analysis were conducted by using qualitative descriptive method. The results revealed that in the end they realized that traveling is always the best way to learn about everything, including about the culture and the ways people seeing the world. In short, there will always be the symbol (relationship between words), the referent (something or the thing it describes), and the meaning (the thought which is related to the word and the thing).